FUN GRAMMAR TEACHING - Kadariyah, Nurlaila (LET: Linguistics, Literature and English Teaching Journal, 2014)
It?s necessary to change our  view that  grammar is taught only as a set of rules making or changing of sentences structure, but grammar is a flexible frame that can be  changed based on the communicative needs. Grammar also can be taught not only by giving explanation and exercises, but grammar can be taught by fun evaluation, games or outdoor activity, song, and poems. These are the ways to increase students? motivation and interested in the material. Our class can be fun and interesting. The important thing in teaching and learning grammar is the students have experience to apply the grammar rules in a real communication and realistic context.